THE EFFECT OF PLYOMETRIC TRAINING ON JUMP HEIGHT IN EXTRACURRICULAR VOLLEYBALL PARTICIPANTS AT SMKN 3 MALANG - Lisa Safriana Mudahyana; Mahmud Yunus (Indonesian Conditioning Coaches, 2026)
This study was conducted to analyze the effect of implementing plyometric training on improving jump height among volleyball extracurricular participants at SMKN 3 Malang. Plyometric training was selected based on its ability to optimize lower-limb muscle explosive power through the stretch-shortening cycle mechanism, which is a key component in volleyball techniques such as smashing, blocking, and jump serving. This study employed an experimental method using a one-group pretest–posttest design involving 14 male participants who followed a six-week training program with a frequency of three training sessions per week. Jump performance data were collected using the Vertical Jump Test with the Jump MD device during the pretest and posttest. The results indicated an increase in jump height for all participants, with improvements ranging from approximately 2 to 6 cm. Normality and homogeneity tests confirmed that the data met the criteria for parametric analysis. The paired t-test revealed a significance value of 0.001 (p < 0.05), indicating that plyometric training had a significant effect on improving jump height. Therefore, plyometric training is recommended as an effective training program to enhance explosive power and jumping ability in student-level volleyball players.